(untitled) (Годишен зборник на Филозофски факултет - Скопје, 2021)
Sexual violence is an important public health problem that affects the well-being of a large proportion of adolescents. The empirical studies indicated that the attitudes towards sexual violence are strong predictors of the likelihood of both perpetrating sexually aggressive acts and being victimized. That is why comprehensive sexuality education, among the other objectives, makes remarkable efforts to inculcate negative attitudes towards violence, particularly sexual, in children and adolescents. This study makes an attempt to shed light on the relation of sexual-violence supportive attitudes, gender norms conformity, and specific knowledge about sexual violence in acceptance of modern myths about sexual violence. Its main objective is to inform curricula developers what are the complex links among these features in order to help them create and deliver efficient programs in comprehensive sexuality education. The study was carried out with 483 participants (43,6% males), at the age range from 18 to 24 (M=21,6, SD=3,0). The results suggest that conformity to certain masculine gender norms in addition to sexist attitudes can help in predicting the endorsement of modern myths about sexual violence. Contrary to the expectations, it has been found that the specific knowledge about sexual violence does not contribute significantly to predicting the criterion variable. Based on the study findings, it is suggested that much more than providing students with relevant information, sexuality education should address and highlight the need for introducing transformative gender identities/roles alongside working on de-constructing gender discrimination.